Contribution in evaluation the procedures for dealing with financial crime and corruption - Kopsidas, Odysseas (Edelweiss Applied Science and Technology, 2024)
This paper deals with an especially important and topical issue: tackling financial crime and corruption. It is important to record and evaluate the legislative framework, which appears to be multilevel, as there are a variety of provisions, which seek to cover all the issues raised. The research is of particular interest in comparatively assessing the changes that have taken place with the new Penal Code, which in general has resolved multiple interpretative issues, leaving some intact. The work is structured in three main sections: (1) in the protection of the Greek state from external intrusions by analyzing the provisions on fraud against public property, (2) in the protection of the Greek state from internal intrusions by analyzing the provisions for infidelity and embezzlement at the expense of public property and (3) in the fight against corruption in the public sector by analyzing the provisions of bribery in the public sector and the influence of trade. At the end, some structural conclusions for the overall legislative framework are recorded.